Examining the effectiveness of information technology in sports psychology interventions: A comprehensive review - Usman Tariq; Pakiza Ikram; Zubair Meera Hussain (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The essential purpose of this research study is to determine the effectiveness related to information technology in sports psychology intervention. This research study depends upon primary data to determine the study and develop different questions. The informative technology is considered the independent variable, and the sport psychology intervention is the main dependent variable. I used smart PLS software to determine the research and generated informative results related to each variable, including independent and dependent. The descriptive statistic analysis, the correlation coefficient, the significant analysis, and the smart PLS algorithm model also explain the graphical analysis between them. The overall research study found that information technology directly and significantly relates to sport psychology interventions.